Understanding the Turnover Intentions of Knowledge Workers: Implications for Team Dynamics and Psychological Well-Being in Sports Organizations - Xin Li; Aili Zou; Gang Qin; Sufang Fan, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Using grounded theory, this study explores the driving mechanisms behind the turnover intentions of knowledge employees. Focusing on "resignation intention," the research subjects were selected based on the definition of knowledge employees. Qualitative research and data analysis were conducted using computer-based grounded theory, employing a three-level coding approach: open coding, pivot coding, and selective coding. This process identified the main categories contributing to harmful turnover tendencies among knowledge employees and facilitated the development of an integrated driving mechanism model. To validate the theoretical framework, interviews with human resource professionals were conducted. A total of 52 data points were coded, summarizing the factors influencing turnover intentions into four primary connection points: "person-post" mismatches, workplace ecology, subjective external evaluations, and external influences. Among these, "person-post" mismatches emerged as the foundational driving factor, while workplace ecology played a key role in the work environment. Together, these factors combine with subjective evaluations to form immediate driving influences, while external conditions were identified as the most likely triggers for turnover. These insights offer potential applications for addressing team dynamics, psychological engagement, and retention strategies, particularly within sports organizations, where cohesive and stable team environments are essential for success.